2005
DOI: 10.1161/01.hyp.0000153305.50128.a1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin Type-1 Receptor Antagonism on Small Artery Function in Patients With Type 2 Diabetes Mellitus

Abstract: Abstract-Endothelial dysfunction has been demonstrated to occur in small arteries from patients with type 2 diabetes and hypertension. The effects of angiotensin II receptor blockade on vessel function were examined using pressure myography in a randomized 12-week double-blind placebo-controlled parallel group study using candesartan cilexitil. The maximal vascular response to acetylcholine (Ach) was impaired at baseline and improved with candesartan. This improvement was primarily caused by an effect in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Blood pressure was higher in control participants, but this was not significant, and, indeed, the structural pattern of wall growth traditionally associated with hypertension was observed in depressed patients. Treatment with angiotensin-converting enzyme inhibitors or calcium channel blockers, which are known to influence small artery endothelial function 21 or wall remodeling, [22][23][24] was similar between the 2 groups of patients studied. Depressed patients were more likely to be taking statins, which can improve small artery endothelial function, 25 but despite this, relaxation to acetylcholine was impaired compared with control participants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Blood pressure was higher in control participants, but this was not significant, and, indeed, the structural pattern of wall growth traditionally associated with hypertension was observed in depressed patients. Treatment with angiotensin-converting enzyme inhibitors or calcium channel blockers, which are known to influence small artery endothelial function 21 or wall remodeling, [22][23][24] was similar between the 2 groups of patients studied. Depressed patients were more likely to be taking statins, which can improve small artery endothelial function, 25 but despite this, relaxation to acetylcholine was impaired compared with control participants.…”
Section: Discussionmentioning
confidence: 76%
“…Small arteries 100 to 150μm in diameter were dissected from the tissue and carefully cleaned under a dissecting microscope. Isolated vessels were then transferred to an arteriographic bath chamber (Living systems Instrumentation) and cannulated as described previously 21 . The chamber was placed on the stage of an inverted microscope and superfused with PSS, gassed with 5% CO 2 /95% air (pH 7.4 to 7.45) at 37°C, at a superfusion rate of 20mL/min.…”
Section: Gluteal Fat Biopsymentioning
confidence: 99%
“…The improvement of acetylcholine-mediated vascular relaxation may be due to increased formation of NO capable of overcoming quenching by superoxide and/or improved formation/ activity of endothelium-derived hyperpolarizing factor. [79][80][81] In this regard, Kihara et al 82 have demonstrated that treatment of diabetic rats with ACEis improves diabetic neuropathy by increasing NO synthase synthesis.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…Glycated hemoglobin, free radicals, and oxidized low-density lipoproteins also quench the effect of NO. In diabetics, autonomic autoregulation is impaired as shown by the deficient endotheliumdependent relaxation to acetylcholine and bradykinin (Malik et al 2005).…”
Section: Introductionmentioning
confidence: 99%